1985
DOI: 10.1161/01.res.56.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Coronary diastolic pressure-flow relation and zero flow pressure explained on the basis of intramyocardial compliance.

Abstract: In the controversy about the mechanisms determining the high zero flow pressures and the further interpretation of coronary diastolic pressure flow relations, this paper takes a stand in favor of intramyocardial compliance as the primary cause of the high zero flow pressures. An attempt has been made to estimate the compliance distribution within the coronary circulation and to show the specific effect of intramyocardial compliance on arterial and venous pressure-flow relations. Since no data are available on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(98 citation statements)
references
References 93 publications
7
90
1
Order By: Relevance
“…29 An elevated Pzf can be found because of capacitive flow from epicardial and particularly intramyocardial microcirculation. 26,30 This interpretation is strongly supported by the observation that coronary venous outflow continues even when pressure has decayed to Pzf. 31 This venous outflow at cessation of inflow has to come from a pool of blood within the microcirculation, which also constitutes the intramyocardial compliance.…”
Section: Diastolic Coronary Pressure-flow Relationsmentioning
confidence: 85%
See 1 more Smart Citation
“…29 An elevated Pzf can be found because of capacitive flow from epicardial and particularly intramyocardial microcirculation. 26,30 This interpretation is strongly supported by the observation that coronary venous outflow continues even when pressure has decayed to Pzf. 31 This venous outflow at cessation of inflow has to come from a pool of blood within the microcirculation, which also constitutes the intramyocardial compliance.…”
Section: Diastolic Coronary Pressure-flow Relationsmentioning
confidence: 85%
“…25 This corresponds with earlier studies in which intramural blood volume was measured in different ways. 26 Moreover, pressure dependence of coronary resistance was clearly demonstrated by experiments in which coronary flow increased when the arterial-venous pressure difference was kept constant by increasing both pressures by the same amount, which is only possible when resistance decreases with pressure. 27 These findings are important because they imply that a stenosis not only adds resistance to flow in the epicardial arteries but additionally impedes myocardial perfusion by increasing microvascular resistance via the passive elastic behavior of the microvascular walls at vasodilation.…”
mentioning
confidence: 98%
“…The compliances C 1 and C2 were 0.013 and 0.254 ml·mmHg Ϫ1 ·100 g Ϫ1 , respectively, while V0,1 and V0,2 were 2.5 and 8.0 ml/100 g (62,65), with a subendocardial-to-subepicardial ratio of 1.14 for both parameters (11,74). In preliminary simulations, we found that accounting for the volume-dependence of compliance using the method described by Bruinsma et al (11) had a negligible effect on coronary flow waveforms (as in Ref .…”
Section: D Model Of Conduit Coronary Arteries Most Sheepmentioning
confidence: 93%
“…Given the general principle that compliance is higher in vascular beds with lower resistance, one might therefore expect weight-corrected intramyocardial compliance to be higher in newborn lambs. However, if we assume that the similar capillary density and luminal area in the LV of newborn and adult sheep (60) implies similar overall vascularity, it follows that weight-corrected vascular volume should be similar in both groups (62). Assuming similar volume distensibility, then in the absence of more firm data it is also reasonable to assume similar vascular compliance in both groups.…”
Section: Model Validationmentioning
confidence: 99%
“…Those studies, performed in conscious dogs, documented a positive coronary zero flow pressure (Pzf) intercept that exceeded venous pressure in the absence of coronary vascular smooth muscle tone; however, in the presence of intact tone Pzf is noticeably lower. The higher Pzf values during vasodilatation could be explained by either a Starling resistor effect within resistance vessels [1] [2] or a compliance effect of intramyocardial vessels [3]. Indeed, both hypotheses postulate that myocardial tissue pressure is partly responsible for genesis of Pzf.…”
Section: Introductionmentioning
confidence: 99%